Simply waltzing on? Reflections on the performance of the Canberra Press Gallery in an era of prime-ministerial instability. Issue 1 (May 2018) - Simons, Margaret; Strangio, Paul
This article draws on interviews with members of the Canberra Press Gallery to reflect on the performance of journalists in reporting recent national leadership instability. This is in the context of claims that reporters assisted in fomenting the instability and were ethically compromised. The increased pace of the news media cycle and the role of social media has caused a 'cacophonous' environment which journalist believe contributes to instability. The journalistic convention of background briefings is both central to the gallery's performance in reporting leadership tensions and the major impediment to an informed assessment of whether journalists have assisted in fanning instability. We find that despite the centrality of the background briefing to the Gallery's work, there is complexity and disagreement about the practice and the ethical standards that apply. This, we suggest, will be of increasing importance, yet the gallery's willingness and ability to reflect on the issues is limited.